The concept of violence and methods to prevent it according to Taha Abdel Rahman - Abdulhadi, Entesar; Abdulzahra, Hussian (Al-Adab Journal, 2025)
Taha Abdel Rahman set out in his vision to treat the phenomenon of violence from the Islamic religion, depending on non-violence methods as it is the best way to reduce the severity of the spread of violence and the most profound treatment in Arab Islamic societies, which includes a culture of dialogue and debate in the best way, acceptance of the different other, and scientific wisdom, in addition to his focus on an important issue, which is The issue of entrusting the trust and responsibility to man by God Almighty, as he wanted to remind the Muslim man that he is entrusted with everything in life. When the fiduciary thought is established, violence will be reduced to the narrowest possible circle. the goal of Taha Abdel Rahman is to destroy the values ​​of Western modernity, considering them a scourge that threatens the human mind in general and the Arab Islamic mind in special , as it drags the Muslim person into imitation and subjection to the West and spreads a culture of violence, but in hidden ways, and this is what does not accept Taha Abdel Rahman, who called for all his research to renew and create Arab-Islamic modernity, this tasks, according to Taha Abdel Rahman, is one of the tasks of the intellectual who is in opposition to Western modernity, which separates religion from other life affairs